Efficiency and Organizational Structure: A Study of Reverse LBOs - MUSCARELLA, CHRIS J.; VETSUYPENS, MICHAEL R. (Journal of Finance, 1990)
ABSTRACT This paper is a report on 72 firms which went public since 1983 but previously underwent a full or divisional LBO. Accounting measures of performance reveal significant improvements in profitability which resulted mainly from these firms' ability to reduce costs. Firms experience dramatic increases in leverage at the LBO, but the leverage ratios are gradually reduced. The evidence is consistent with the hypothesis that the change in the governance structure of these firms towards more concentrated residual claims created a new organizational structure which is more efficient than its predecessor.